Being in two minds: accommodating emotional victim narratives in Dutch courtrooms - Bosma, Alice Kirsten (Frontiers in Sociology, 2024)
When Victim Impact Statements (VISs) were introduced in Dutch criminal law in 2005, victims were required to limit their statement to the impact of the harm done by the crime. In 2016, a major amendment lifted this restriction. Even though the statement may (still) not be used as legal evidence, critics worried that the change in scope would invite heightened levels of emotion into the courtroom, which would in turn undermine magistrates’ objectivity. A comprehensive evaluation of the old/restricted legislation and a follow-up analysis of courtroom observations showed that the Dutch system was rather well-equipped to accommodate the expressive function of the VIS before 2016. These studies pay some attention to emotional labor to show how emotional narratives were being dealt with in the courtroom. Recently, a new evaluation of the VIS (post-2016) has been carried out. Observation data of this recent study is qualitatively analyzed and compared to previous findings. The paper also gives insight in the way magistrates manage emotionality in the courtroom in relation to perceptions of objective decision making. Results show that, despite the fact that balancing emotion work with safeguarding objectivity introduces feelings of uncertainty, magistrates accommodate empathy between themselves and the victim, but also open up a space for empathy between the defendant and the victim.